Random Coding Bound for E-capacity Region of Asymmetric Broadcast Channel With Stochastic Encoding - Afshar, Nasrin (Mathematical Problems of Computer Science, 2021)
E-capacity (rate-reliability) region of the asymmetric broadcast channel with stochastic encoding is studied. The asymmetric broadcast channel involves two discrete memoryless channels with a common input. A common message is transmitted to both receivers and one private message to the intended receiver. We derive an inner bound for rate-reliability region.